The overall structure of microbiota in patients with adenocarcinoma stomach and colon cancer - O. V. Movchan (Kazimierz Wielki University, 2020)
Introduction Accumulating evidence suggests that the human bowel microbiota contributes to the etiology of colorectal cancer (CRC) and stomach cancer, not only via the pro-carcinogenic activities of specific pathogens but also via the influence of the wider microbial community, particularly its metabolome. The aim of the study The aim of this study was to analyzes the overall structure of microbiota in patients with adenocarcinoma of colorectal and the stomach and healthy controls. Results The studies suggested that colorectal cancer and stomach cancer develops from the complex interactions between inherited susceptibility and environmental factors, there a strong association between adenomatous polyps and some pathogenic bacteria are the precursors of the vast majority of colorectal cancers and stomach. Thus, the data suggested the development of intestinal dysbiosis in patients with adenocarcinoma, which was characterized by inhibiting obligate protective microflora and activation opportunistic microorganisms on the base of carbohydrates, fats, and proteins metabolism disturbances and accumulation of toxic metabolic products that may be an important pathogenetic factor of tumor tissue activation, induction, proliferation, and metaplasia. Significant accumulation of biogenic amines (methylamine, serotonin, histamine) is a leading metabolic profile of microflora inpatient with adenocarcinoma and may have a predictive value for diagnosis, pathogenetic therapy, and determination of food nutrients role in the mechanisms of cancer formation, as well as identifying populations of cancer risk. Conclusions The composition of the tumor microbiome differed from that of adjacent non-neoplastic tissue. The subsite-specific alterations in the colorectal carcinoma and stomach cancer microbiota. There is a high incidence of colorectal cancer and stomach cancer associated with Streptococcus Bovis. These results suggested that the mucosa-associated microbiota is dynamically associated with colorectal carcinoma, which may provide evidence for microbiota-associated diagnostic, prognostic, preventive, and therapeutic strategies for colorectal carcinoma and stomach cancer.